Environmental Policy with Green Consumerism - Stefan Ambec; Philippe De Donder (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Is green consumerism beneficial to the environment and the economy? To shed light on this question, we study the political economy of environmental regulations in a model with neutral and green consumers where the latter derive some warm glow from buying a good of higher environmental quality produced by a profit-maximizing monopoly, while the good bought by neutral consumers is provided by a competitive fringe. Consumers unanimously vote for a standard set at a lower than first-best level, or for a tax delivering the first-best environmental protection level. Despite its under-provision of environmental protection, the standard dominates the tax from a welfare perspective due to its higher productive efficiency, i.e., a smaller gap between the environmental qualities of the two goods supplied. In stark contrast, voters unanimously prefer a tax to a standard when the willingness to pay for greener goods is small enough.
Keywords: D24; D62; Q41; Q42; Q48; 330; environmental regulation; corporate social responsibility; green consumerism; product differentiation; tax; standard; green label; political economy